Pharmaceutical Policies in OECD Countries Reconciling Social and Industrial Goals - Jacobzone, Stephane (OECD Publishing, 2000)
Regulation of the pharmaceutical sector needs to reconcile private and social objectives. Public intervention pursues multiple goals which relate to both health and industry policy. Many OECD Governments are also heavily involved as buyers of pharmaceuticals in publicly-financed health care systems. This paper describes recent trends in pharmaceutical expenditure and financing in a first chapter. A second chapter discusses the economics of pharmaceutical markets. A third chapter provides a review of national policies and their attempts to balance public and private objectives. Pharmaceutical expenditure has been rising steadily as a share of GDP since 1970. However, total health expenditure has also risen. As a result, pharmaceutical expenditure has, on average, maintained its share of total health expenditure in the OECD, close to 15 %. Across countries, pharmaceutical expenditure per capita depends on relative incomes but is also influenced by institutional features. The pharmaceutical ...
Keywords: Social Issues/Migration/Health